Features of functioning of the institution of the parliamentary opposition in the modern world - Duzbaev, Т.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
In this scientific article, the author tried to study the features of the representation of the opposition in the parliaments of developed and developing countries. The opposition in parliament contributes to the development of democracies in the state. Unfortunately, even in the developed EU countries, the representation of the opposition in the state parliament remains low. In a parliamentary democracy, deputies elect the head of government, deputies from the same party or deputies with the same goals often form a parliamentary group. These factions are called coalition factions, or coalition for short. In addition to the coalition, there is also opposition in parliament. The word «opposition» means «oppose». The opposition often disagrees with the ruling coalition and the government. Therefore, she often keeps a close eye on whether the government is doing well. The task of the opposition is to control the work of the government. The opposition can also show that it has other better solutions. A strong opposition is important for the development of democracy. The opposition expresses its opinion in parliament. Opposition outside parliament is also possible. This article demonstrates the tendency towards skepticism towards parliamentary opposition in developed countries. Parliamentary democracy relies on the functioning of the parliamentary opposition because the subjects of the opposition perform their control tasks in front of the public. The opposition in parliament can act like a minority acting according to predetermined characteristics and should be able to control the government and influence legislative output. The other approach, on the contrary, rejects the idea of an active role of the opposition in the decision-making process and cooperation with the ruling majority. Its sole function is to present itself as an alternative future government. This structure allows the opposition to publicly criticize the authorities and immediately demonstrate to the electorate an alternative worthy of the authorities. A system where the opposition does not participate in the decision-making process, usually not considered overly friendly to the opposition, proves exceptionally strong and reliable in times of party fragmentation when it comes to the rights of the opposition.